Green synthesis of silver nanoparticles using Oxalis griffithii extract and assessing their antimicrobial activity - Shivali Singla; Abhishek Jana; Reena Thakur; Chinu Kumari; Sachin Goyal; Joohee Pradhan (Elsevier, 2022)
The silver nanoparticles were successfully synthesized by using Oxalis griffithii's methanolic leaf extract as a reducing agent and aqueous silver nitrate as the precursor. Nowadays, physical and chemical methods are widely used for the synthesis of nanoparticles, but unfortunately, these methods are expensive and not at all eco-friendly. This study highlights the cost effective, eco-friendly, and green synthesis of nanoparticles and also analyses the anti-bacterial effects of the synthesized nanoparticles. The synthesized nanoparticles were analyzed by various methods and techniques like UV-Vis spectroscopy, FTIR, particle size, Zeta potential, FE-SEM, EDX, and antimicrobial activity. The prepared silver nanoparticles show a characteristic absorption peak in UV-Vis spectroscopy due to the SPR (surface plasmonic resonance) band between 408 and 412 nm wavelengths. Particle size by XRD and Dynamic Light Scattering was in the nanometer range, which was further confirmed in FE-SEM, which also proved its spherical shape and crystalline nature. The stability of the AgNPs was determined by the Zeta potential. The antimicrobial activity of silver nanoparticles was compared to that of pathogenic microorganisms Bacillus subtilis and E. coli, and the results demonstrated that the synthesized AgNPs are effective against both microorganisms.